The role of museums and galleries in the formation of cultural landscapes and tourism - Trushaj, Aleks (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
This study evaluates cultural landscapes and tourism in Kazakhstan, Kyrgyzstan, Albania and Ukraine, based on a survey of 443 residents. The cultural landscape ratings are: Astana (4+), Bishkek (2–3), Tirana (4–5), and Kyiv (3.5). Cultural tourism development is rated as follows: Astana (3), Bishkek (3–4), Tirana (4–5), and Kyiv (3). The cultural landscape and tourism are influenced by political power, national identity, economic development, tourist interest, cultural carriers, historical monuments, infrastructure, and investment in culture. The survey also examines preferences, visit frequency, and accessibility of cultural institutions. Kyiv sees the highest visit frequency, while Bishkek has the lowest. Museums, galleries, cinemas, theatres, and cultural parks are key destinations, but many respondents report low accessibility and inclusivity. Lists of cultural institutions were created for mapping the cities' main attractions.
Keywords: accessibility; cultural exchange; cultural institutions; cultural map of the city; dostopnost; kulturna izmenjava; kulturne ustanove; kulturni zemljevid mesta; nacionalna identiteta; national identity